2018
DOI: 10.1116/1.5049141
|View full text |Cite
|
Sign up to set email alerts
|

Responding to the growing issue of research reproducibility

Abstract: An increasing number of studies, surveys, and editorials highlight experimental and computational reproducibility and replication issues that appear to pervade most areas of modern science. This perspective examines some of the multiple and complex causes of what has been called a “reproducibility crisis,” which can impact materials, interface/(bio)interphase, and vacuum sciences. Reproducibility issues are not new to science, but they are now appearing in new forms requiring innovative solutions. Drivers incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Some sub-disciplines in science only require a single analytical/measurement tool or just a few tools for a complete analysis of their systems. In contrast, materials analysis generally requires multiple advanced-characterization techniques to obtain an appropriate understanding of a new thin film or material (Baer & Gilmore, 2018). These techniques typically require an understanding of the physics and chemistry behind them, can be performed in multiple modes, and often require detailed first-principles and/or established empirical/semi-empirical modeling for their data reduction.…”
mentioning
confidence: 99%
“…Some sub-disciplines in science only require a single analytical/measurement tool or just a few tools for a complete analysis of their systems. In contrast, materials analysis generally requires multiple advanced-characterization techniques to obtain an appropriate understanding of a new thin film or material (Baer & Gilmore, 2018). These techniques typically require an understanding of the physics and chemistry behind them, can be performed in multiple modes, and often require detailed first-principles and/or established empirical/semi-empirical modeling for their data reduction.…”
mentioning
confidence: 99%
“…Although recommendations for improving repeatability in research have been developed (6)(7)(8)(9), it is not clear if they apply in a simple way to all fields. Before attempting to form recommendations appropriate for materials chemistry, or to decide if they are even needed, it is valuable to gather quantitative data related to experimental replicability.…”
mentioning
confidence: 99%
“…found that 65% of those responding identified reproducibility as a significant issue [7]. As described by Baer and Gilmore [8],…”
Section: Reproducibility Problemsmentioning
confidence: 99%
“…Such issues challenge research teams and the review process. Systematic and sustained efforts are needed to address the causes of reproducibilityproblems that can hinder the rate of scientific progress and lower public and political regard for science[8].…”
mentioning
confidence: 99%